Kajian Kriminologi Terhadap Kasus Pembunuhan Seorang Bayi Oleh Ibu Kandung - Dian Wulan Ramadhani; Johny Krisnan; Basri Basri; Yulia Kurniaty (Borobudur Law and Society Journal, 2022)
Unwanted pregnancies often end in unlawful acts such as illegal abortions, murder, or the disposal of the baby by the birth mother. Therefore, this study aims to find out "How is the chronology of the perpetrator (who is a mother) to kill a baby who is her flesh and blood?" and "What is the driving factor for the crime of infanticide by the birth mother?". To obtain data, the writer conducted an interview with Mrs. Ratih Mannul Izzati, SH., MH. as the Panel of Judges of the Magelang District Court and conducted a study on the Decision on Case Number 16/Pid.Sus/2021/PN Mgg. The results of this study indicate that the chronology of the perpetrators of killing their babies by trying to have an abortion in early pregnancy but without success. Then on the day the baby was born, the perpetrator killed the baby by putting camphor into the baby's mouth and then strangling it until it suffocated; and the driving factor for the perpetrator of the murder of the baby was a pregnancy out of wedlock which resulted in fear of an illicit relationship with his lover being exposed, because the perpetrator was an only child who was the hope of his parents, besides that the perpetrator was also a victim of the irresponsibility of the man who impregnated him, the reason economy, and panic when finding a newborn baby crying.